PENINGKATAN DISIPLIN BELAJAR SANTRI MELALUI BIMBINGAN DAN KONSELING - Anggie Meiliyana Putri; Lalis Lalis; Rizka Apriliana; Muhamad Rifa’i Subhi (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
This study aims to determine the increase in discipline of learning santri through guidance and counseling. The scope of the study refers to: obedience at the time of entrance of activities, obedience and compliance to the rules in the pesantren, completing the tasks of teachers in boarding schools, coaching sanctions for those who violate. The research method using Descriptive Qualitative Research, with data collection techniques in the form of observation and interview. The subjects of the study were santri in Pondok Pesantren Al-Hadi Min Ahlisunnah Wal Jamaah Pekalongan. The results showed that the discipline of learning santri low, so that the boarding school pesantren impose a system of punishment on students who are not disciplined. Students feel bound by the rules but do not implement and comply with the rules that apply in the boarding school. Through the role of boarding school board members in providing guidance and counseling services using behavioral approach, able to improve the discipline of learning santri.